Dilemma Pembentukan Institusi Bank Tanah: Pemerataan Sosial Atau Pertumbuhan Ekonomi - Anantya Prianggoro, Afwan; Widodo Dwi Pramono, Retno (Jurnal Syntax Fusion, 2023)
The major agenda of Indonesia's land management program is agrarian reform that consolidates and distributes land for social justice. However, instead of strengthening existing institutional institutions, Indonesia established a new institution called a land bank, which provides land to boost the investment climate and economy. For some people, the purpose of establishing a land bank is to exacerbate land use management practices in Indonesia because it is at odds with the goals of agrarian reform. Thus, a big question arises that needs to be answered, what are the advantages and disadvantages of land bank practice in Indonesia? To answer this big question, this research aims to identify the advantages and disadvantages of land bank practice in Indonesia. By identifying the advantages and disadvantages of land bank entities, the output of this study is expected to provide recommendations to improve the quality of land bank practices. This research is a case study with a qualitative approach using descriptive analysis. Secondary data sources include scientific publication data, mass media articles, online seminars, interviews, and focus group discussions. The study results show that the advantage of establishing a land bank is solving various land, spatial and environmental problems, while the disadvantage of land bank is that it can potentially exacerbate land-grabbing practices. Thus, from the findings of land bank losses, the government should clarify the functions and objectives of land banks to improve the socio-economic welfare of the Indonesian people.